Transition to circular and sustainable economy through design - Camocho, David João Geraldes (2022)
The evolution of society and the increase in consumption of products to meet more and more consumer needs is taking society to a breaking point that, if surpassed, will hardly have a return, jeopardizing the future generations. Since the mid-1970s, it has been realized that the current model is unsustainable and that a new approach to production and consumption is needed towards a more sustainable society with added value for all stakeholders in the value chain. In this context, designers have a fundamental role in the development of innovative and sustainable solutions that meet the needs of both consumers, producers, and society in general. Currently, the Circular Economy is seen as an approach to Sustainability with great potential for success and which is being the target of numerous research and development projects and initiatives, of practical application in companies, public funding, and education. However, despite all efforts in this direction, there is still a large gap between theory and practice. There is a need to support the practice of Design with methods and tools that allow the transposition of circularity strategies in the development of effective solutions that result in sustainable and circular products and services adjusted to the needs of all actors involved in the value chain. In order to meet these needs, the research carried out in this PhD Thesis resulted in the development of the Rounding the vertices, Design for the Circular Economy toolkit, which includes a set of practical implementation tools, aligned with the Design process and which is also a didactic tool to support designers in their projects and in the identification and development of innovative and circular solutions for projects.